European Monetary Measures to Support Economic Recovery - Munteanu, Bogdan (European Journal of Multidisciplinary Studies, 2017)
The present article aims to look at the current monetary measures deployed by ECB to address the economic context of below expectations economic growth and inflation, taking into account the expression of monetary policy via the Expanded Asset Purchase Programme. This tool is used to push financial liquidity into the economies of the European Union, in a banking system affected by the crisis and which has been shown to be still at risk by the latest stress tests conducted by the European Banking Authority. The article points out why monetary measures are important to support the economic recovery in Europe, in an interventional context of monetary and fiscal policies of governing authorities, appealing to economic models to explain how the policies contribute to economic growth and development. The methodology used by the article is economic analysis and rationale, cost-benefit analysis, statistics of money market and banking industry indicators, etc. The conclusion emerging from this article is that the Asset Purchase Programme of ECB led in a certain degree to an improvement in the macro-economic environment on yields and on its transmission channels into the financial system and into economies.